SAKHA’ DALAM PERSPEKTIF HADIS - Farid Naya (IAIN Ambon, 2017)
Among the concrete manifestation of sensitivity sense to others are pleased or like to share upon the ownership right of one person to other. Because, the ownership essentially relative. Given the ownership is absolute belongs only to God. Man is basically just received a mandate to find, manage and utilize what they have just to meet their needs, and recommended does not forget to charity. People who likes to give, basically he has instilled goodness and invest for the future. If this to be the principle in social relations, at least it can provide a hope for the elimination of poverty, the eradication of ignorance, the reach of backwardness, the political stability, the increased of economic growth, the guarantee of security and so forth. This article will analyze the hadith associated with the generosity (sakha). Key words: sakha, generosity, hadith.